Student Mentoring Through Dance Performance to Enhance Artistic Competence in Islamic Early Childhood Education - Faizatul Faridy; Rani Puspa Juwita; Siri Leik (CV Berkah Syahdin Trust, 2025)
Background: The development of artistic competence among students of Islamic Early Childhood Education (PIAUD) is an essential component in preparing professional and creative early childhood educators. However, opportunities for practical engagement that integrate artistic skills with real performance contexts remain limited. Aims: This community service program aims to enhance students’ artistic competence through mentoring activities integrated with dance performance and evaluation in a collaborative art event. Methods: This program employed a Service Learning approach, which integrates academic learning with direct community engagement. The implementation stages included preparation, mentoring, performance practice, and evaluation. Data were collected through observation, performance assessment, and documentation, and analyzed descriptively to evaluate the effectiveness of the program. Result: The results showed that student participation in mentoring and dance performance activities significantly improved their artistic competence, including creativity, confidence, teamwork, and performance skills. In addition, students demonstrated increased ability to express ideas through movement and respond to evaluative feedback constructively. Conclusion: The Service Learning-based mentoring program effectively enhances the artistic competence of PIAUD students and provides meaningful experiential learning. This approach contributes to strengthening practical skills and supports the development of professional competencies in early childhood education.